The Impact of Vitamin D Deficiency on Coronary Artery Disease Severity Based on Myocardial Perfusion Imaging: A Cross-Sectional Study - Mahdi Haghighatafshar; Behnaz Shekasteband; Tahereh Firuzyar; Zahra Etemadi; Farinaz Farhoudi; Mesbah Shams (Iranian Journal of Medical Sciences)
Background: The impact of low levels of vitamin D (Vit D) on the severity of cardiovascular diseases has become a significant challenge. This study aimed to assess this impact.Methods: This pilot cross-sectional study enrolled two hundred patients referred to Namazi Hospital, Shiraz, Iran for myocardial perfusion imaging in 2019. The assessment included myocardial perfusion imaging and Vit D level evaluation. Quantitative ischemia analysis utilized Estimated Summed Stress Scores (SSS), Summed Rest Scores (SRS), and Summed Difference Scores (SDS). Myocardial Perfusion Imaging (MPI) results were categorized into normal, mild ischemia, moderate ischemia, and severe ischemia based on estimated SSS. Ischemia severity was aligned with established criteria, designating severe quantitative ischemia as SSS>13. Vit D was categorized using cutoffs at 10, 20, and 30 ng/mL. Mann–Whitney U-test was used for quantitative variables and Chi Square test for qualitative variables. Results: Chi Square test revealed a significant association between categorized Vit D levels below 10 ng/mL and severe ischemia (SSS>13) (P<0.001). Total Vit D level and also categorized Vit D with cut-offs of 10, 20, and 30 ng/mL showed no association with abnormal MPI. SSS was notably higher in patients with Vit D levels below 10 ng/mL (P=0.026).Conclusion: The findings of this study emphasize an association between Vit D level below 10 ng/mL and severe myocardial ischemia, as indicated by SSS.